2004
DOI: 10.2166/wst.2004.0869
|View full text |Cite
|
Sign up to set email alerts
|

Stirred anaerobic sequencing batch reactor containing immobilized biomass: a behavior study when submitted to different fill times

Abstract: The effect of the filling stage on the behavior of a mechanically stirred anaerobic sequencing batch reactor containing biomass immobilized on 1 cm polyurethane foam cubes was investigated. The reactor was made of acrylic with a capacity of 6.3 L, treating per cycle 2.5 L synthetic low-strength wastewater with a concentration of 500 mgCOD/L, at 30+/-1 degrees C. Eight-hour cycles (tC) and agitation of 500 rpm were utilized. At the beginning of each cycle 60% of the wastewater volume was treated, sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
12

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
1
7
0
12
Order By: Relevance
“…Within this context, it should be mentioned that Ratusznei et al [3] verified that composition and concentration used in the synthetic influent indicated that reduction in efficiency occurred due to probable exposure to air and formation of extracellular polymers, especially at longer fill times (t F /t C ) and not due to the possibility of toxic effects, according to results obtained by Borges et al [4]. Results of profiles run during the operation cycle of organic matter, BA and TVA confirmed non-occurrence of toxic effects.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Within this context, it should be mentioned that Ratusznei et al [3] verified that composition and concentration used in the synthetic influent indicated that reduction in efficiency occurred due to probable exposure to air and formation of extracellular polymers, especially at longer fill times (t F /t C ) and not due to the possibility of toxic effects, according to results obtained by Borges et al [4]. Results of profiles run during the operation cycle of organic matter, BA and TVA confirmed non-occurrence of toxic effects.…”
Section: Resultsmentioning
confidence: 74%
“…The synthetic wastewater used in their work was based on carbohydrates (sucrose, starch, and cellulose), protein (meat extract), lipids (soy bean oil) at a total concentration of 500 mgCOD/L, and sodium bicarbonate (200 mg/L). Formation of extracellular polymers was minimized when the biomass was not exposed to air according to results obtained by Borges et al [4]. Since in the assays with sanitary wastewater no extracellular polymers were formed even at longer fill times, it is believed that the composition of the synthetic wastewater likely stimulated in some way formation of these polymers.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Estudos sobre a influência de variáveis de processo sobre a eficiência e estabilidade do reator anaeróbio operado em batelada sequencial quando aplicado ao tratamento de diferentes efluentes têm sido encontrados em literatura, como os relacionados: (i) ao tipo de mistura, a qual poderá ser implementada por recirculação da fase líquida (Brito et al, 1997;Camargo et al, 2002;Bergamo et al, 2009;Bezerra et al, 2009) ou por agitação mecânica (Angenent et al, 2002;Rodrigues et al, 2003;Rodrigues et al, 2004;Damasceno et al, 2008;Michelan et al, 2009); (ii) ao tempo de enchimento ou estratégia de alimentação (Bagley e Brodkorb, 1999;Shizas e Bagley, 2002;Borges et al, 2004;Orra et al, 2004;Zimmer et al, 2008;Albanez et al, 2009); e (iii) à carga orgânica (Ng, 1989;Massé e Masse, 2000;Chebel et al, 2006;Damasceno et al, 2007;Oliveira et al, 2008;Friedl et al, 2009;Oliveira et al, 2009;Novaes et al, 2010).…”
Section: Revisão Bibliográficaunclassified
“…Estudos sobre a influência de variáveis de processo sobre a eficiência e estabilidade do reator anaeróbio operado em batelada e/ou batelada alimentada sequenciais contendo biomassa granulada ou imobilizada em suporte inerte (ASBR ou AnSBBR) quando aplicado ao tratamento de diferentes efluentes têm sido encontrados em literatura, como os relacionados: (i) ao tipo de mistura, a qual poderá ser implementada por recirculação da fase líquida (CAMARGO et al, 2002;BERGAMO et al, 2009;BEZERRA et al, 2009) ou por agitação mecânica (RODRIGUES et al, 2003(RODRIGUES et al, e 2004DAMASCENO et al, 2008;MICHELAN et al, 2009;NOVAES et al, 2010a); (ii) ao tempo de enchimento ou estratégia de alimentação (SHIZAS; BAGLEY, 2002;BORGES et al, 2004;ORRA et al, 2004;ALBANEZ et al, 2009;NOVAES et al, 2010b;OLIVEIRA et al, 2010;RODRIGUES et al, 2011); e (iii) a carga orgânica (MASSÉ;MASSE, 2000;CHEBEL et al, 2006;DAMASCENO et al, 2007;OLIVEIRA et al, 2008;FRIEDL et al, 2009;OLIVEIRA et al, 2009;CARVALHINHA et al, 2010).…”
Section: Revisão Bibliográficaunclassified